Creencias y matemáticas - De Faria Campos, Edison (2008)
Research about beliefs has experienced a large impulse starting from the decade of the 80s. The works of McLeod (1988, 1992, 1994) have shown that the affective questions play a fundamental role in the teaching and the learning of mathematics, that some of them are strongly ingrained in the individual and that they are not easily changed by instructions (Gómez-Chacón 2000). In the article I will discuss the concept of beliefs in mathematics and explain the meaning of beliefs or of systems of beliefs. Finally, I will describe some important beliefs on the nature of mathematics.